PENGARUH MOTIVASI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA DI SMA BINA PUTERA KELAS 11-A - Siti Nabila Rahmah; Desty Endrawati Subroto; Siti asiyah; Aliya Febriyanti; Cahya Maulidya; Reva Paulina Djodi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to analyze the influence of parental motivation on student learning achievement. The motivation referred to in this research is high expectations, excessive motivation, and comparison with friends or other relatives. The research was conducted using quantitative methods involving 40 students from 1 class at SMA BINA PUTERA Serang Regency. The research results show that there is a significant or continuous relationship between motivation from parents and student learning achievement, where the greater the pressure the student receives, the lower the academic achievement achieved. Apart from that, other factors such as emotional support and good communication between parents and children also influence this relationship.